2004
DOI: 10.3748/wjg.v10.i13.1995
|View full text |Cite
|
Sign up to set email alerts
|

Safe major abdominal operations: Hepatectomy, gastrectomy and pancreatoduodenectomy in elder patients

Abstract: AIM:To evaluate the impact of advanced age on outcome after hepatectomy, gastrectomy and pancreatoduodenectomy. METHODS:Two hundreds and eleven patients undergone hepatectomy, gastrectomy and pancreatoduodenectomy from January 1998 to September 2002 were analyzed retrospectively. Clinicopathologic features and operative outcome of 83 patients aged 65 years or more were compared with that in 128 younger patients aged less than 65 years. RESULTS:The nutritional state, such as pre-operation level of serum albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 17 publications
(13 reference statements)
0
13
0
Order By: Relevance
“…Infection rates for patients with complex procedures are estimated between 2.9% and 13.0% [12]. These classifications are easy to apply but might not reflect the actual risk for post- [24] showed pancreatoduodenectomy and hepatectomy with resection of more than two segments being independent factors for major post-operative complications. Despite both being complex surgical procedures, the odds ratio (OR) differed notably (3.77, p = 0.0006 for pancreatoduodenectomy versus 1.08, p = 0.03 for hepatectomy).…”
Section: Discussionmentioning
confidence: 99%
“…Infection rates for patients with complex procedures are estimated between 2.9% and 13.0% [12]. These classifications are easy to apply but might not reflect the actual risk for post- [24] showed pancreatoduodenectomy and hepatectomy with resection of more than two segments being independent factors for major post-operative complications. Despite both being complex surgical procedures, the odds ratio (OR) differed notably (3.77, p = 0.0006 for pancreatoduodenectomy versus 1.08, p = 0.03 for hepatectomy).…”
Section: Discussionmentioning
confidence: 99%
“…Many publications have suggested that major abdominal surgery due to cancer can be performed safely in elderly patients with good results and the preoperative selection must be based on physiologic criteria and performance status rather than on chronological aspects [2,15,16]. However, in the publication of Polanczyk et al [1], in which 4315 patients were included and stratified into 4 age groups, after adjusting for functional status and type of surgery, they concluded that elderly patients have an increased risk of postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…With the advancement of surgical techniques and perioperative management, hepatectomy has been regarded as the most effective and commonly used treatment for HCC. Although some studies have found significantly higher morbidity or mortality after hepatectomy for HCC in elderly patients, 2–7 comparable surgical outcomes with younger patients have also been reported 8–17 . There has been one report on the safety and feasibility of hepatectomy for HCC patients aged 80 years or more 17 .…”
Section: Introductionmentioning
confidence: 99%